Interrelations Between Astrochemistry and Galactic Dynamics - Mendoza, Edgar; Duronea, Nicolas; Ronsó, Daniele; Corazza, Lia C.; van der Tak, Floris; Paron, Sergio; Nyman, Lars-Åke (Frontiers in Astronomy and Space Sciences, 2021)
This paper presents a review of ideas that interconnect Astrochemistry and Galactic Dynamics. Since these two areas are vast and not recent, each one has already been covered separately by several reviews. After a general historical introduction, and a needed quick review of processes like the stellar nucleosynthesis which gives the base to understand the interstellar formation of simple chemical compounds (e.g. H$_2$, CO, NH$_3$ and H$_2$O), we focus on a number of topics which are at the crossing of the two big areas, Dynamics and Astrochemistry. Astrochemistry is a flourishing field which intends to study the presence and formation of molecules as well as the influence of them into the structure, evolution and dynamics of astronomical objects. The progress in the knowledge on the existence of new complex molecules and of their process of formation originates from the observational, experimental and theoretical areas which compose the field. The interfacing areas include star formation, protoplanetary disks, the role of the spiral arms and the chemical abundance gradients in the galactic disk. It often happens that the physical conditions in some regions of the interstellar medium are only revealed by means of molecular observations. To organise a rough classification of chemical evolution processes, we discuss about how astrochemistry can act in three different contexts: namely, $i.$ the chemistry of the early universe, including external galaxies, $ii.$ star forming regions, and $iii.$ asymptotic giant branch (AGB) stars and circumstellar envelopes. We mention that our research is stimulated by plans for instruments and projects, such as the on-going Large Latin American Millimeter Array (LLAMA), which consists in the construction of a 12m sub-mm radio telescope in the Andes. Thus, modern and new facilities can play a key role in new discoveries not only in astrochemistry but also in radio astronomy and related areas. Furthermore, the research of the origin of life is also a stimulating perspective.